Validação de um método analítico empregando GC-MS para a determinação de ácidos haloacéticos em amostras de água potável - Chiavelli, Lucas Ulisses Rovigatti (2011)
During the water disinfection process with chlorine and its derivatives, several organic by-products, including, haloacetic acids (HAAs), are formed. The HAAs represent the major class of non-volatile halogenated by-products. Nine are the species of these acids that occurs more commonly in tap water: the monochloroacetic acid (MCAA), dichloroacetic acid (DCAA), trichloroacetic acid (TCAA), monobromoacetic acid (MBAA), dibromoacetic acid (DBAA), tribromoacetic acid (TBAA), bromochloroacetic acid (BCAA), bromodichloroacetic acid (BDCAA) and chlorodibromoacetic acid (CDBAA). Some of these compounds are toxic for humans, animals and plants. Recent studies have demonstrated the association between some types of cancer developments with the HAAs exposure. The main agency that regulates these compounds is the Environmental Protection Agency U.S. (EPA), which establishes a maximum contaminant level of 60 μg L-1 for the concentrations sum of five haloacetic acids (HAA5: MCAA, DCAA , TCAA, MBAA and DBAA) in treated water. The purpose of this study was to validate a method using GC-MS technique for determination of HAAs in drinking water. The method of extraction/derivatization was adapted from the USEPA Method 552.3. After optimization of the system analysis parameters, the standard curves were constructed, with values of R2 > 0.99. The detection limits found for the nine HAAs were from 0.42 to 1.17 μg L-1. In the intra-day repeatability study were obtained RSD values between 0.35 and 5.73%. Recovery tests with samples showed recovery rates between 69.87 and 107.32%, consistent with the literature values. Drinking water samples were collected in six different locations in the city of Maringá-PR, being six samples from the public supply systems and two from artesian well. The concentration of HAA5 in the samples ranged from 0.63 (± 0.05) to 13.30 (±0.28) μg L-1, thus the obtained concentrations are within the limits set by USEPA.